www.previnalesao.com.br: website com orientações para cuidadores sobre prevenção de lesões por pressão em idosos acamados em domicílio - Silva, Ana Paula Teles Cameli Rodrigues Da [UNIFESP] (2018)
Introduction: With the increase in life expectancy, a higher number of chronical conditions emerge. Some diseases can cause skin changes, leaving elderly people more vulnerable to the development of Pressure Lesions (PL). In this sense, it is necessary to direct care and attention to the bedridden elderly to prevent PL. Objective: Develop and validate a website with orientation for caregivers on the prevention of pressure lesions in elderly bedridden at home. Methods: Study for the development and validation of a website for orientation regarding elderly bedridden at home. The study was approved by the Ethics in Research Committee of UNIFESP, no 1343/20106 and CAAE 60565616.3.0000.5505. Literature search was conducted using the following databases: Scielo, Pubmed and Google Scholar research engine. No website was found with this intent. Subsequently, the website was developed. The bibliographic content was done on the Scielo and Pubmed databases and Google Scholar research engine, between the years of 2007 and 2017. The searched themes was elderly skin, definition, risk factors, prevention, support surface, incontinence and caregivers. Scientific articles, books and international consensus were used to develop the content of the website. A domain was acquired and registered in the Dot BR Information and Coordination Center. The WordPress platform was used to construct and manage the content of the website. Validation was done in two stages. In the first stage, the Delphi Method was used, applying an evaluation instrument on which the Content Validity Index was used. In the second stage, the target public was consulted to verify the opinion of caregivers concerning the organization of the website, writing style, appearance and motive. The Likert Scale was used to measure the percentage of agreement on the aspects of the instrument and its items. Results: The website was denominated www.previnalesao.com.br, using a language for easy understanding for the caregivers of the elderly. It presents none topics for the orientation of concepts, risk factors and prevention of PL. Using the Content Validity Index (CVI), validation obtained 90% of approval. Conclusion: A website was developed with orientations on the prevention of PL for the caregivers of elderly patients bedridden at home (www.previnalesao.com.br).